Assessment of the Utility of Chitosan in Drug Delivery of Sulfamethoxazole - Nussara Soontorntepwarakul; Kanokthip Boonyarattanakalin; Kasama Srirussamee; M. Paul Gleeson (My University, 2024)
The objective of this research was to develop chitosan (CS) nanoparticles (NP) and microfibres (MF) for oral delivery applications related to low solubility drugs. The ionic gelation method in conjunction with freeze-drying was used to produce crosslinked chitosan material. Dynamic light scattering (DLS) was used to characterize particle size and polydispersity index (PDI). Surface morphology was analyzed using scanning electron microscopy (SEM). The antibiotic drug sulfamethoxazole (SMO) was loaded onto the chitosan nano/micro material. The degree of loading, loading efficiency and the release kinetics were investigated using high-performance liquid chromatography (HPLC) and UV-visible spectrophotometry, respectively. We found that CS nanoparticles have the potential to improve the delivery properties of SMO due to their more rapid release compared to microfibres or traditional tablet formulations.
Keywords: Pneumocystis jirovecii pneumonia detection and treatment; Multicomponent Synthesis of Heterocycles; Advanced Drug Delivery Systems